Mindfulness, posttraumatic stress symptoms, depression, and social functioning impairment in Chinese adolescents following a tornado: Mediation of posttraumatic cognitive change. (January 2018) - Xu, Wei; Fu, Gan; An, Yuanyuan; Yuan, Guangzhe; Ding, Xu; Zhou, Yuyang
Abstract: Previous studies have shown that mindfulness is associated with less negative traumatic outcomes in people who experienced traumatic events. The present study investigated how mindfulness is related to posttraumatic stress disorders (PTSD) symptoms, depression and social functioning impairment in Chinese traumatized adolescents by considering the role of posttraumatic cognitive change (PCC). A total of 247 Chinese adolescents, who had experienced a severe tornado six months prior to this study, were recruited to complete a series of questionnaires. Results showed that the proposed model fitted the data very well (χ 2 = 16.200, df = 8, χ 2 /df = 2.025, GFI = 0.983, CFI = 0.991, TLI = 0.976, RMSEA = 0.063). Further analyses revealed that PCC mediated the relation between dispositional mindfulness and all negative posttraumatic outcomes (including PTSD symptoms, depression and social functioning impairment). Limitations, clinical implications, and directions for future research were discussed. Highlights: Participants are 247 Chinese tornado youth survivors. Mindfulness was negatively correlated with negative posttraumatic outcomes. Mindfulness was negatively correlated with negative cognitive change. Negative cognitive change positively correlated with negative posttraumatic outcomes. Cognitive change mediated the mindfulness - negative posttraumatic outcomes link.